(3TQM aUhd CHbQGWs - (3CHhYeQGf ehSi Hf YHjO Gddg GdbQWHis; (3ehSi Hf YHjO Gddg Hf ejehf GdbQWHj, CHh YeQGf,J (B601 (3g` s
(3ChdgG (B:s
(3eG CXf ef GdYdeGA GdPjf CdahG GdcJH , hCda cJGHkG ai fhY ef CfhGY GdYdhe , hgh jbUO GdG jage cJGHg MJi jTQM s
(3BNQgG (B:s
(3bGd CHbQGW (B: (3GdaQb GdcHjQ GdPi jLQi OGFekG bhd GdeaSQ Ef GdQWhHI JSJaQZ ef Gdbhi HGdbF , hef GdVYja HGdESgGd ,dG jWQO Pdc OGFekG ,hbO YdeJ WQjbJg , hbO Tc LGdjfhS ai gPG GdaUd gd gh dCHbQGW Ch dZjQg ? s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3fSNI SGOSI ai SHY ebGdGJs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B132 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B273 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs